THE DEVELOPMENT OF THE STUDENTS’ COMMUNICATIVE COMPETENCE IN THE PROCESS OF THE FOREIGN LANGUAGE PROFESSION ORIENTED STUDY - Boichevska, Ilona; Veremiuk, Liudmyla (Збірник наукових праць Уманського державного педагогічного університету, 2018)
The article deals with the development of the students’ communicative competence in the process of the foreign language profession oriented study. The aim of the article is the investigation of the essence, the purpose, the ways of realization and the results of the communicative competence development during the profession oriented study of foreign languages. It has been determined that profession oriented study of the foreign language is supposed to be the study, in the centre of which there are students’ needs in foreign language learning with the orientation on the peculiarities of the future profession and specialty. The author defines that one of the main demands of the professional oriented study of the foreign language is the necessity to make the content and the methods of its teaching closer to the future practical and professional needs of students. It has been also said that the main aim of the foreign language study at the higher educational establishment is the development of the linguistic, cross-cultural and communicative competence. It has been stated that different approaches are used in the practice of the profession oriented foreign languages communication teaching.